An influence of initial swimming training technology on technical preparedness indicators of children with consequences of cerebral palsy - Босько, Василь (Slobozhanskyi Herald of Science and Sport, 2017)
Vasiliy Bosko Purpose: to develop an innovative technology of elementary swimming training in the backstroke way of children with the consequences of infantile cerebral palsy (ICP) and to evaluate its effectiveness. Material & Methods: methods were used: analysis of scientific and methodological literature, pedagogical experiment, expert evaluation, statistical methods. The pedagogical experiment involved 29 children diagnosed with cerebral palsy, of which two groups were formed: an experimental group consisting of 14 children, 6 of them with spastic diplegia and 8 with a hemiparetic form, and a control group of 15, of which 6 – with spastic diplegia and 8 – with a hemiparetic form of cerebral palsy. After the experiment, we conducted an expert survey in order to identify the experts' opinion on the level of mastering the technique of swimming by backstroke way of children with the consequences of infantile cerebral palsy. Results: main means of implementing the technology is the web-based information system "SwimCP (Swimming with Cerebral Palsy)" developed by us, which promotes the effective learning of the swimming of children with the effects of infantile cerebral palsy in the initial stage of sports training by selecting and recommending an orienting set of exercises, in accordance with the specific form of infantile cerebral palsy and the stage of learning motor action. Conclusion: with the help of expert assessment confirmed that the proposed technology is the initial training to swimming by backstroke way to children with consequences of cerebral palsy is effective.